2014
DOI: 10.1186/1752-1947-8-137
|View full text |Cite
|
Sign up to set email alerts
|

Meniscal tear as potential steering factor for inflammation may aggravate arthritis: two case reports

Abstract: IntroductionMeniscal tear is thought to play a crucial role in onset as well as progression of arthritis. However, role of cytokine response to meniscal injury and resulting inflammation is not clearly understood. Because synovial fluid is juxtaposed to cartilage and serves as a biological connection between chondrocytes and synoviocytes, we chose synovial fluid analysis to ascertain biochemical response associated with a meniscal tear.Case presentationWe report the cases of two patients with clinically differ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…We found ten cases of an “erroneous” Biblical eponym with the name “Lazarus” (five articles) [ 39 43 ], for example, “CDH was first described in 1679 by Lazarus Riverius” [ 39 ], “They were first described by Lazarus and Trombetta in 1978” [ 42 ], and “ Lazarus and Chiang examined patients that had a bone marrow transplant later followed by a solid organ” [ 43 ]. There were four cases of “pseudo” Roman eponyms with the name “Hercules” (four articles) [ 44 47 ], for example, “After incubation at room temperature for ten minutes, the absorbance was measured at 540 nm in a spectrophotometer (Bio-Rad Laboratories, Hercules , CA, USA)” [ 45 ], and one case for “Venus”: “We report the unusual case of a girl diagnosed with Neisseria gonorrhoeae after bathing in a heavily frequented hot pool at the edge of the crater lake Specchio di Venere (“Mirror of Venus ”) on Pantelleria Island, Italy” [ 48 ]. As a result, we did not include the eponym “the Hercules complex” from Roman mythology [ 36 ] in our study.…”
Section: Discussionmentioning
confidence: 99%
“…We found ten cases of an “erroneous” Biblical eponym with the name “Lazarus” (five articles) [ 39 43 ], for example, “CDH was first described in 1679 by Lazarus Riverius” [ 39 ], “They were first described by Lazarus and Trombetta in 1978” [ 42 ], and “ Lazarus and Chiang examined patients that had a bone marrow transplant later followed by a solid organ” [ 43 ]. There were four cases of “pseudo” Roman eponyms with the name “Hercules” (four articles) [ 44 47 ], for example, “After incubation at room temperature for ten minutes, the absorbance was measured at 540 nm in a spectrophotometer (Bio-Rad Laboratories, Hercules , CA, USA)” [ 45 ], and one case for “Venus”: “We report the unusual case of a girl diagnosed with Neisseria gonorrhoeae after bathing in a heavily frequented hot pool at the edge of the crater lake Specchio di Venere (“Mirror of Venus ”) on Pantelleria Island, Italy” [ 48 ]. As a result, we did not include the eponym “the Hercules complex” from Roman mythology [ 36 ] in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Patients who sustain an intra-articular joint injury are at greater risk of suffering from future cartilage degeneration due to a complex interaction between mechanical and biological factors [ 2 ]. Beyond ACL tears, lesions to the meniscus and posterior cruciate ligament, as well as intra-articular osseous fractures, are common injuries requiring surgical treatment [ 2 , 16 , 17 , 18 , 19 ]. Uncontrolled inflammation, through the upregulation of TNF-α, IL-1β, and IL-6, remains even after surgical stabilization and places the injured joint in a catabolic environment [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…We also note that for constant therapeutic effect, drug concentration may be ‘traded-off’ with the dissociation constant. It has been reported that IL-1α levels in synovial fluid increases significantly following traumatic injury to cartilage tissue [14, 92, 93]. The results presented here show that even small molecules with a very strong negative charge (MW = 3 kDa and Z d = -16) can completely inhibit IL-1α mediated aggrecan catabolism provided it binds strongly to IL-1α with a dissociation constant of 10 nM or smaller (see Fig 6 and Table 5).…”
Section: Discussionmentioning
confidence: 99%